Analisis Penerapan Akuntansi Manajemen Terhadap Kinerja Keuangan Perusahaan - Anggi Oktapiani; Deby Irama; Frida Aprilia Pratiwi; Mike Della Ayu Rahmawati; Noviana Ayu Anjar Dewi; Oktiana Nurul Fadilah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to analyze the Application of Management Accounting to Company Financial Performance. This research uses qualitative research with a literature study research method. The research results show that the application of management accounting which includes finance, production and marketing will help each division manager start and make definite decisions. So the application of management accounting needs to be implemented on an ongoing basis with the aim of implementing maximum financial performance for each company. Focusing on financial performance, management accounting will provide precise information based on company data in financial reports and journals which will also be used as insight into non-financial performance. The usefulness of executive bookkeeping relies on the idea of ​​proper administration and bookkeeping, in introducing monetary data that is useful for the organization to carry out the most practical arrangement, supervision, direction and portion of assets, thus requiring good administration. The application of accounting management in a company found that to see financial performance it was necessary to measure financial conditions using data and information from the company's annual financial report each year.